Effects of oral administration of synthesized δ-amides of eflornithine in the rat - Helena, Kevin J.; N’Da, David D.; Johansson, Carl C.; Breytenbach, Jaco C.; Ashton, Michael (Arzneimittelforschung, 2010)
The purpose of this study was to synthesize a series of δ-amide derivatives of the antitrypanosomal drug eflornithine (2,5-diamino-2-(difluoromethyl)pentanoic acid hydrochloride, DMFO, CAS 70052-12-9), to determine their physicochemical properties and to assess whether they convert to eflornithine in vivo and if so, whether higher systemic exposure to eflornithine could be achieved by increase intestinal absorption, suggesting an oral treatment to be possible. The derivatives were synthesized by amidation of eflornithine on its δ-amino group using acyl chlorides. The partition coefficients (log D, pH = 7.4) were found to be between −0.78 ± 1.07 and −0.07 ± 1.08 while the aqueous solubility (Sw), which as determined in phosphate buffered solution (pH 7.4), ranged from 11.13 ± 0.32 to 28.74 ± 0.36 mg/mL. The synthesized compounds were thus mostly more lipophilic than eflornithine itself (log D = −0.98 ± 0.88, Sw = 34.96 ± 0.37 mg/mL). The intestinal absorption was assessed by plasma analysis after oral administration of each compound to Sprague-Dawley rats. The biological data revealed that the derivatives were either not absorbed from the gastro-intestinal tract or not metabolized into eflornithine as no parent drug was detected in the plasma.
Keywords: Amidation; Antitrypanosomal drug; CAS 70052-12-9; Eflornithine, oral bioavailability; Human African trypanosomiasis (HAT)